INTEGRATED SCIENCE EDUCATION AS A SOLID FOUNDATION IN SCIENCES, TECHNOLOGY, ENGINEERING, MATHEMATICS, AND EDUCATION (STEME): A TOOL FOR SUSTAINABLE DEVELOPMENT - DELPHONSO, BAMIDELE TOKUNBO; OSUNLOYE , OLAWALE ADEJUMO; ABOLOJI , TOYIN JOY; SUNDAY , ERNEST FRANK; JAIYESIMI , OLADELE OMOTAYO; LAWAL, ABDULAFEEZ SEWANU (Sokoto Educational Review, 2025)
This paper focuses on the crucial role of Integrated Science Education in achieving sustainable development. The significance of Science, Technology, Engineering, Mathematics, and Education (STEME) in building a sustainable future cannot be overstated. STEME serves as a key catalyst for achieving sustainable development goals. This paper acknowledges the pivotal role of STEME in driving the scientific and economic development of any nation. The paper investigates the objectives and benefits of integrated science education, including its role in promoting scientific, technological, and engineering advancements. It explores the rationale for incorporating integrated science into the junior secondary school curriculum. The 21st century has witnessed rapid advancements in Information Science and Technology, including Artificial Intelligence (AI), across all aspects of life. To effectively adapt to these developments, we must embrace and foster scientific and technological experimentation that will drive national sustainable development. Based on this premise, the paper strongly advocates for the inclusion of STEME within the integrated science curriculum. Furthermore, the teaching of integrated science at all levels should be closely linked to real-life situations. DOI: https://doie.org/10.0218/SER.2025764280